Environmental impact categories of hydrogen and ammonia driven transoceanic maritime vehicles: A comparative evaluation - Bicer, Yusuf; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this study, carbon-free fuels-ammonia and hydrogen-are proposed to replace heavy fuel oils in the engines of maritime transportation vehicles. Also, it is proposed to use hydrogen and ammonia as dual fuels to quantify the reduction potential of greenhouse gas emissions. An environmental impact assessment of transoceanic tanker and transoceanic freight ship is implemented to explore the impacts of fuel substituting on the environment. In the life cycle analyses, the complete transport life cycle is taken into account from manufacture of transoceanic freight ship and tanker to production, transportation and utilization of hydrogen and ammonia in the maritime vehicles. Several hydrogen and ammonia production routes ranging from municipal waste to geothermal options are considered to comparatively evaluate environmentally benign methods. Besides global warming potential, environmental impact categories of marine sediment ecotoxicity and marine aquatic ecotoxicity are also selected in order to examine the diverse effects on marine environment. Being carbon-neutral fuels, ammonia and hydrogen, yield significantly minor global warming impacts during operation. The ecotoxicity impacts on maritime environment vary based on the production route of hydrogen and ammonia. The results imply that even hydrogen and ammonia are utilized as dual fuels in the engines, the global warming potential is quite lower in comparison with heavy fuel oil driven transoceanic tankers. Geothermal energy sourced hydrogen and ammonia fuelled transoceanic tankers release about 0.98 g and 1.65 g CO2 eq. per tonne-kilometer, respectively whereas current conventional heavy fuel oil tanker releases about 5.33 g/tonne-kilometer CO2 eq. greenhouse gas emissions. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Clean fuels; Hydrogen; Ammonia; Maritime transportation; Environmental impact assessment; LIFE-CYCLE ASSESSMENT; COMBUSTION CHARACTERISTICS; EMISSIONS; TECHNOLOGIES; FUEL; TRANSPORT; PRESSURE; PORTS; Chemistry; Electrochemistry; Energy & Fuels